2012
DOI: 10.1021/jf302706e
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Agricultural Biotechnology Crop Product: Testing from Discovery to Commercialization

Abstract: "Genetically modified" (GM) or "biotech" crops have been the most rapidly adopted agricultural technology in recent years. The development of a GM crop encompasses trait identification, gene isolation, plant cell transformation, plant regeneration, efficacy evaluation, commercial event identification, safety evaluation, and finally commercial authorization. This is a lengthy, complex, and resource-intensive process. Crops produced through biotechnology are the most highly studied food or food component consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 11 publications
0
35
0
1
Order By: Relevance
“…There are numerous rigorous selection and quality control steps that ensure a lack of unintended effects in newly developed GM crops (Privalle et al, 2012). Moreover, the development of new GM maize hybrids is, at its core, a conventional breeding venture involving extensive backcrossing steps to ensure a high degree of genetic similarity to elite, high performing commercial germplasm.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous rigorous selection and quality control steps that ensure a lack of unintended effects in newly developed GM crops (Privalle et al, 2012). Moreover, the development of new GM maize hybrids is, at its core, a conventional breeding venture involving extensive backcrossing steps to ensure a high degree of genetic similarity to elite, high performing commercial germplasm.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, genetic engineering requires prior knowledge of the desired gene(s) for introduction into the plant. Several recent articles provide an overview of the GM crop development process from discovery through commercialization (Privalle et al, 2012;Mumm, 2013;Prado et al, 2014;NAS, 2016). The first step in the development of a GM crop is to identify a gene that confers the desired characteristic (referred to as a "trait" in GM crops).…”
Section: Breeding Of Gm Crops Sources Of Candidate Genes For Gm Cropsmentioning
confidence: 99%
“…When genetic engineering of plants was first being developed, it was hypothesized that this technology might induce potentially unintended changes that affect food or feed safety-for example, by activating previously dormant pathways in the plant (Kessler et al, 1992). As a result, extensive regulatory requirements for GM crops, which use a comparative safety assessment process, are now in place (König et al, 2004;Cellini et al, 2004;EFSA, 2006;Paoletti et al, 2008;CODEX, 2009;Privalle et al, 2012;Hoekenga et al, 2013;Prado et al, 2014). Since that time, numerous studies have found that GM varieties are compositionally equivalent to conventional crops Herman and Price, 2013;Hoekenga et al, 2013;Ricroch, 2013;Xu et al, 2014;Ladics et al, 2015aLadics et al, , 2015bCurran et al, 2015;Venkatesh et al, 2015Venkatesh et al, , 2016.…”
Section: Plant Selection Practices Minimize Unsafe Unintended Changesmentioning
confidence: 99%
“…Compared to the traditional techniques of conventional crossbreeding and induced mutagenesis, the transgenic techniques have permitted the realisation of specific desirable traits that often would not be available in the natural gene pool of the individual species (Privalle et al, 2012). Transgenesis was also expected to speed up the breeding process and enable release of new varieties with novel beneficial traits but instead, the approval of GMOs is time-and finance-consuming due to legal obligations (Fichtner et al, 2014;Araki and Ishii, 2015).…”
Section: Genome Editing Using Sdns: An Outlookmentioning
confidence: 99%